Assembly sequences plan generation using features simplification. (May 2018) - Hadj, Riadh Ben; Belhadj, Imen; Trigui, Moez; Aifaoui, Nizar
Highlights: Automatic generation of assembly sequences plans from CAD model. Simplification of the CAD which reduces the calculation time. Automatic extraction of the required data from the CAD. Abstract: The automatic generation of the assembly/disassembly plan is considered a topical problem in the computer-aided tools area. The main problem of the major proposed approaches is the excessive processing time to treat the whole assembly model. This paper proposes a simplification approach of CAD models to make the generation of assembly plan easy. The developed method begins by the elimination of connection elements to obtain a simplified assembly sequence. A case-based reasoning algorithm is, then, developed to insert the entire eliminated elements in the global assembly sequence plan. Two examples of CAD assembly are treated in order to compare and validate the obtained results.